1998
DOI: 10.1103/physrevlett.80.2485
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Chaos in Neural Spike Trains

Abstract: Recently, it has been shown that interspike interval (ISI) series from driven model neurons can be used to discriminate between chaotic and stochastic inputs. Here we extend this work to in vitro experimental studies with rat cutaneous mechanoreceptors. For each of the neurons tested, we show that a chaotically driven ISI series can be distinguished from a stochastically driven ISI series on the basis of a nonlinear prediction measure. This work demonstrates that dynamical information can be preserved when an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In neural systems (real and modeled) driven by chaotic and by random stimuli, it has been shown that the determinism in the driving signal is retained (as assessed by predictability) after passing through simple neural dynamics and an embedding procedure (20,23). Thus it has been demonstrated that important dynamic information is conserved in a state-space reconstruction of discrete-time data.…”
Section: Methodsmentioning
confidence: 99%
“…In neural systems (real and modeled) driven by chaotic and by random stimuli, it has been shown that the determinism in the driving signal is retained (as assessed by predictability) after passing through simple neural dynamics and an embedding procedure (20,23). Thus it has been demonstrated that important dynamic information is conserved in a state-space reconstruction of discrete-time data.…”
Section: Methodsmentioning
confidence: 99%
“…It is an intriguing problem whether ISI reconstruction of a deterministic input is applicable to real biological neurons which are certainly more complex in dynamics than the integrate-and-®re model. The validity of the ISI reconstruction has been tested by numerical simulations for neuron models of various complexities (Racicot and Longtin 1997), by the eect of noise (Lindner et al 1998), and by physiological data of in vitro rat cutaneous mechanoreceptors (Richardson et al 1998). There has also been an attempt at reconstruction using threshold-crossing intervals (Janson et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This can be seen by comparison with Figure 3. Figure 8 shows an example of input signal reconstruction which estimates I input using ISI vectors of the described in Equation 15. We used a time delay T = 1, an embedding dimension d E = 7, and a local linear map for H(y(j)).…”
Section: Numerical Resultsmentioning
confidence: 99%